Address on the conclusion of the third session of the Dublin Statistical Society - Larcom, Thomas A. (Statistical and Social Inquiry Society of Ireland, 1851)
It is usual and desirable that at the close of each session of our Society, when we pause for a time in the prosecution of our labours, we should look generally at the position we have attained, and, suspending for the evening the reading of new papers, consider the whole session as a page in our existence closed. To what purpose have we met? What progress have we made? Are our labours proceeding in a right direction? May we from the past gather hope for the future? I think we may; we have ample ground for hope.
Read June 18th 1850
Keywords: Dublin Statistical Society; Irish economic conditions; 314.15